Usaha Kesehatan Gigi dan Mulut (UKGS) pada Sekolah Binaan TK Negeri Pembina Kendari - Erwin, Erwin; Pujirahayu, Rahminingrum; Nurhati, Tri; Asmawati, Asmawati; Sumi, Sumi (JCSE: Journal of Community Service and Empowerment, 2023)
Preschool students are vulnerable to dental health problems and poor dental hygiene behavior. Dental health issues in children can have an impact on their growth, development, and learning. Therefore, it is necessary to pay attention and provide intensive methods of health services to preschool students, namely by providing dental health services directly in schools through the school's dental health business program. The method of implementing this community service activity is the provision of dental health services for school students, assisted by the Kendari City Pembina State Kindergarten. Activities carried out from September to December 2017, the activities carried out are limited to promotive, preventive, and curative services. The results of the activity showed that students' knowledge about dental health increased, changes in dental health maintenance behavior became better, and limited curative treatment could be carried out well. It is recommended that these activities be carried out continuously, in stages, and the forms of activities developed to provide greater and long-term benefits.